Small Sensitivity to Temperature Variations of Si-Photonic Mach–Zehnder Interferometer Using Si and SiN Waveguides - Hiraki, Tatsurou; Fukuda, Hiroshi; Yamada, Koji; Yamamoto, Tsuyoshi (Frontiers in Materials, 2015)
We demonstrated a small sensitivity to temperature variations of delay-line Mach–Zehnder interferometer (DL MZI) on a Si photonics platform. The key technique is to balance a thermo-optic effect in the two arms by using waveguide made of different materials. With silicon and silicon nitride waveguides, the fabricated DL MZI with a free-spectrum range of ~40 GHz showed a wavelength shift of -2.8 pm/K with temperature variations, which is 24 times smaller than that of the conventional Si-waveguide DL MZI. We also demonstrated the decoding of the 40-Gbit/s differential phase-shift keying signals to on-off keying signals with various temperatures. The tolerable temperature variation for the acceptable power penalty was significantly improved due to the small wavelength shifts.